Implementasi Platform Web Dalam Aplikasi Monitoring Pertumbuhan Balita Dengan Metode Agile Scrum Studi Kasus: Posyandu Desa Pisangan Jaya - Saepul Fajar; Devi Yunita (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2026)
Monitoring toddler growth is an essential activity to ensure optimal health and development from an early age. However, the recording process at Posyandu Aster 7, Pisangan Jaya Village, is still carried out manually using KIA/KMS books and Excel sheets, which often leads to data entry errors, duplication, and limited access to information for cadres and parents. This condition decreases efficiency and causes delays in reporting. This study aims to implement a web-based platform called Kembangku as a toddler growth monitoring application developed using the Laravel framework and the Agile Scrum methodology. This method was chosen because it is adaptive and allows the system to be developed iteratively through sprints involving users such as Posyandu cadres and mothers. The application focuses on digital data recording, secure data storage, and real-time information access. The system testing was conducted using three methods: black box testing to ensure that all functions operated according to user requirements, white box testing to verify program logic and code accuracy, and user satisfaction testing using the Likert scale. The results show that all system functionalities worked properly without logical errors and achieved an average user satisfaction score of 4.55, categorized as “Strongly Agree.” In conclusion, the Kembangku application is feasible to be used as a digital medium for monitoring toddler growth. It improves efficiency, accuracy, and transparency in data recording and provides convenience for both cadres and parents in monitoring children’s development in real-time.